Harmonic distortion analysis of triple gate SOI nanowire MOSFETS down to 100 K. (December 2017) - Paz, B.C.; Doria, R.T.; Cassé, M.; Barraud, S.; Reimbold, G.; Vinet, M.; Faynot, O.; Pavanello, M.A.
Abstract: The linearity of triple gate nanowire transistors (NWs) implemented on a Silicon-On-Insulator (SOI) substrate is investigated in this work considering temperature (T) influence. The analysis is performed in long channel nanowire MOSFETs with different fin width (WFIN ), from quasi-planar structures (WFIN  = 10 μm) to narrow devices (9.5 nm), operating as single-transistor amplifiers from room temperature down to 100 K. The total, second and third order harmonic distortions (THD, HD2 and HD3, respectively) are extracted using the Integral Function Method (IFM). The analysis is divided in two parts. First, a fixed input signal is applied at the gate of the single-transistor amplifiers and, then, the output signal is fixed. Transport parameters such as effective mobility (μeff ), mobility degradation coefficient (θ) and series resistance (RS ) have been extracted down to 100 K and correlated to the distortion to explain linearity peaks behavior with temperature and fin width. Narrow transistors have shown improved linearity mainly due to higher intrinsic voltage gain (AV ) considering the entire temperature range. Low temperature operation has shown to degrade the linearity characteristics of both wide and narrow NW MOSFETs. Highlights: Harmonic distortion of long channel triple gate nanowires implemented on SOI substrates decreasing temperature down to 100 K Temperature and fin width influence on total, second and third order harmonic distortion Experimental analysis performed for both fixed input and fixed output signals, considering single-transistor amplifiers Experimental evidence of transport parameters connection to distortion minima Demonstration of linearity degradation with temperature decrease and fin width increase